2012
DOI: 10.1007/s00199-012-0712-4
|View full text |Cite
|
Sign up to set email alerts
|

Is there a plausible theory for decision under risk? A dual calibration critique

Abstract: Acknowledgements Financial support was provided by the National Science Foundation (grant numbers IIS-0630805 and SES-0849590). Helpful comments and suggestions were provided by an anonymous referee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…Leading critics of EUT include Kahneman and Tversky (1979) and more recently Rabin (2000) and Rabin and Thaler (2001), who consider the weight of evidence against EUT sufficient to label it an 'exhypothesis'. In contrast, argues a case against probability weighting of the PT form, and more recently, the unfavourable implications for EUT from the concavity-calibration argument of Rabin (2000) have been challenged by Cox and Sadiraj (2006) and Cox et al (2013) on the grounds that calibration arguments lead to equally problematic implications for nonlinear probability weighting. Furthermore, models in which outcomes are weighted by functions of probabilities have also been challenged at the process level (Fiedler and Glöckner 2012).…”
Section: Introductionmentioning
confidence: 86%
“…Leading critics of EUT include Kahneman and Tversky (1979) and more recently Rabin (2000) and Rabin and Thaler (2001), who consider the weight of evidence against EUT sufficient to label it an 'exhypothesis'. In contrast, argues a case against probability weighting of the PT form, and more recently, the unfavourable implications for EUT from the concavity-calibration argument of Rabin (2000) have been challenged by Cox and Sadiraj (2006) and Cox et al (2013) on the grounds that calibration arguments lead to equally problematic implications for nonlinear probability weighting. Furthermore, models in which outcomes are weighted by functions of probabilities have also been challenged at the process level (Fiedler and Glöckner 2012).…”
Section: Introductionmentioning
confidence: 86%
“…We can therefore follow Wei and Stocker, and assume a prior for θ with a density function given by f (θ), the function used above to characterize the inhomogeneity in the discriminability of nearby orientations. 11 This means that if we work in terms of the transformed state variableθ ≡ F (θ), the prior distribution forθ is uniform.…”
Section: Noisy Coding Of Sensory Magnitudesmentioning
confidence: 99%
“…However, empirical evidence on the presence of RP is scarce, only a handful of empirical studies are available that tested RP, all in the economic domain. First, Cox, Sadiraj, Vogt, and Dasgupta (2013) observed RP preferences for financial outcomes in an incentive-compatible study. Second, Bleichrodt et al (2017) identified the causes of RP empirically, showing how a reference-dependent model with loss aversion may explain RP (as already suggested by Rabin, 2000).…”
mentioning
confidence: 99%